Vaccines for Canine Leishmaniasis - Palatnik-De-Sousa, Clarisa B. (Frontiers in Immunology, 2012)
Leishmaniasis is the third most important vector-borne disease worldwide. Visceral leishmaniasis (VL) is a severe and frequently lethal protozoan disease of increasing incidence and severity due to infected human and dog migration, new geographical distribution of the insect due to global warming, coinfection with immunosuppressive diseases, and poverty. The disease is an anthroponosis in India and Central Africa and a canid zoonosis (ZVL) in the Americas, the Middle East, Central Asia, China, and the Mediterranean. The ZVL epidemic has been controlled by one or more measures including the culling of infected dogs, treatment of human cases, and insecticidal treatment of homes and dogs. However, the use of vaccines is considered the most cost–effective control tool for human and canine disease. Since the severity of the disease is related to the generation of T-cell immunosuppression, effective vaccines should be capable of sustaining or enhancing the T-cell immunity. In this review we summarize the clinical and parasitological characteristics of ZVL with special focus on the cellular and humoral canine immune response and review state-of-the-art vaccine development against human and canine VL. Experimental vaccination against leishmaniasis has evolved from the practice of leishmanization with living parasites to vaccination with crude lysates, native parasite extracts to recombinant and DNA vaccination. Although more than 30 defined vaccines have been studied in laboratory models no human formulation has been licensed so far; however three second-generation canine vaccines have already been registered. As expected for a zoonotic disease, the recent preventive vaccination of dogs in Brazil has led to a reduction in the incidence of canine and human disease. The recent identification of several Leishmania proteins with T-cell epitopes anticipates development of a multiprotein vaccine that will be capable of protecting both humans and dogs against VL.